Water Quality Assessment Using Water Quality Index (WQI): A Case Study of Karmanasha River, Lalitpur, Nepal - Luhar, Pankaj Prakash; Sharma, Isha; Shrestha, Leena (International Journal on Engineering Technology, 2025)
The research analyzes the water quality of Karmanasha River which functions as a primary water source for domestic and agriculture needs in Lalitpur area. This investigation examines the environmental well-being of the river through the analysis of measurements for pH, Electrical Conductivity (EC), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Iron Content, Turbidity (NTU), and Total Coliform Count which were analyzed and then aggregated in the form of WQI. The BOD and COD levels demonstrate substantial human-caused polluting factors. This research highlights the Water Quality Index to indicate the quality of water in the Study area.